2021
DOI: 10.1002/adhm.202100024
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Decellularized Extracellular Matrix Derived from 3D Stem Cell Spheroids under Macromolecular Crowding Serves as a Scaffold for Tissue Engineering

Abstract: Scaffolds for tissue engineering aim to mimic the native extracellular matrix (ECM) that provides physical support and biochemical signals to modulate multiple cell behaviors. However, the majority of currently used biomaterials are oversimplified and therefore fail to provide a niche required for the stimulation of tissue regeneration. In the present study, 3D decellularized ECM (dECM) scaffolds derived from mesenchymal stem cell (MSC) spheroids and with intricate matrix composition are developed. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 66 publications
(40 reference statements)
0
35
0
Order By: Relevance
“…For a determination of the effect of spheroid size on therapeutic potential, a method that can fabricate spheroids with the desired diameters must be used. Herein, by controlling the number of cells seeded into each well of MC hydrogel-coated plates [5][6][7][8][9], we could precisely manipulate the size of the formed spheroids, which is crucial for ensuring the consistency of the following therapeutic effect after cell transplantation. The harvested MSC spheroids contained abundant matrix components, including fibronectin, laminin, collagen, and HSPG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a determination of the effect of spheroid size on therapeutic potential, a method that can fabricate spheroids with the desired diameters must be used. Herein, by controlling the number of cells seeded into each well of MC hydrogel-coated plates [5][6][7][8][9], we could precisely manipulate the size of the formed spheroids, which is crucial for ensuring the consistency of the following therapeutic effect after cell transplantation. The harvested MSC spheroids contained abundant matrix components, including fibronectin, laminin, collagen, and HSPG.…”
Section: Discussionmentioning
confidence: 99%
“…Among the developed methods, we [5][6][7][8][9] and others [2,3,[10][11][12] have reported that culturing MSCs in a three-dimensional (3D) multicellular spheroid configuration can significantly enhance both the viability of administered MSCs and their overall therapeutic functions. Specifically, the spheroid configuration can more closely recapitulate the physiological 3D microenvironment than conventional two-dimensional (2D) cultures [3].…”
Section: Of 13mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the activity of tyrosinase, the cells prepared according to the aforementioned methods were lysed with RIPA buffer (20 mM Tris-HCl, 1 mM EGTA, 150 mM NaCl, and 1% Triton X-100) [69] at 4 • C for 20 min followed by centrifugation at 14,000 rpm for 15 min. A bicinchoninic acid assay (G-Biosciences, St. Louis, MO, USA) was used to quantify the total protein of the supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…To tackle the ongoing challenge of obtaining a renewable and robust supply of human cardiac dECM, one group has looked towards the use of cardiac organoids as a cultured source for dECM. Chiang et al used organoids derived from human umbilical cord blood mesenchymal stem cells to lay down a structural protein niche that was then decellularized to provide a dECM scaffold ( Chiang et al, 2021 ). The resulting dECM was shown to possess both essential microarchitecture and functional bioactivity ( Chiang et al, 2021 ).…”
Section: Emerging Researchmentioning
confidence: 99%